Akuntabilitas dan Transparansi Pengelolaan ZIS pada Badan Amil Zakat Nasional Provinsi Kalimantan Selatan - Berliana Maharani; Basyirah Ainun; Mochammad Arif Budiman; Mahyuni (Indonesian Journal of Applied Accounting and Finance, 2024)
The low level of public trust in zakat management institutions has resulted in suboptimal zakat collection. One of the efforts to enhance public trust in zakat institutions is the implementation of a robust accounting system in zakat fund management. Proper accounting management is expected to enable zakat management organizations (OPZ) to manage zakat more effectively, efficiently, transparently, and accountably. This study employs a descriptive method with a qualitative approach to analyze the level of accountability and transparency in the National Zakat Agency (BAZNAS) of South Kalimantan Province. Data collection techniques include interviews and secondary data obtained from BAZNAS South Kalimantan Province. The findings indicate that BAZNAS South Kalimantan Province has demonstrated accountability and transparency in financial reporting, providing information related to activities and programs, auditing financial reports, preparing financial statements in accordance with applicable sharia accounting standards, and utilizing information technology in managing Zakat, Infaq, and Sadaqah (ZIS) funds. Additionally, the agency has consistently submitted accountability reports to the Governor, the Ministry of Religious Affairs, and the BAZNAS of the Republic of Indonesia.